HUBUNGAN POWER OTOT LENGAN DAN KORDINASI MATA TANGAN TERHADAP KETERAMPILAN SERVIS ATAS BOLA VOLI PADA SISWA EKSTRAKURIKULER BOLA VOLI SMAN 16 BANDAR LAMPUNG - Dwi Al Muzakki; Joan Siswoyo; Muhammad Fajril Rifaldo; Candra Kurniawan (STKIP Subang, 2026)
This study aims to determine the relationship between arm muscle power and hand-eye coordination on the overhand serve skill in volleyball among extracurricular students at SMA Negeri 16 Bandar Lampung. The study used a quantitative method with a correlational approach. The population consisted of 20 students, all of whom were included as the sample using total sampling technique. The instruments used were a pull and push dynamometer to measure arm muscle power, a ball toss and catch test to measure hand-eye coordination, and a test to assess the overhand serve skill in volleyball. The results showed that: 1) There is a significant relationship between arm muscle power and overhand serve skill with a correlation of r.hitung 0,638 > r.tabel 0,444, indicating that the better the arm muscle power, the higher the serve ability of the students. 2) There is a significant relationship between hand-eye coordination and overhand serve skill with a correlation of r.hitung 0,716 > r.tabel 0,444. 3) There is a significant relationship between arm muscle power, hand-eye coordination, and overhand serve skill with a correlation of r.hitung 0,742 > r.tabel 0,444. This study emphasizes that the success of overhand serve skills in volleyball depends on both physical strength and proper movement coordination.